Approximation of Periodic Functions in Weighted Lorentz Spaces - Yildirir, Yunus Emre; Avsar, Ahmet Hamdi (Sarajevo Journal of Mathematics, 2017)
In the present work, the approximation properties of means of trigonometric Fourier series in weighted Lorentz spaces with weights satisfying the so called Muckenhoupt's A_p conditions are investigated.